Transformative Pathways: Fostering Leadership Development Through Reflective Undergraduate Education - Stawnychko, Leda (Imagining SoTL, 2025)
Undergraduate education can play a transformative role in developing students’ leadership capacities, the practice of which can be examined through the Scholarship of Teaching and Learning. This study examines how educational experiences in a senior undergraduate-level leadership development course at a western Canadian university contributed to shaping students’ self-awareness, personal philosophies, and leadership skills.Using thematic analysis of reflective writing from 17 students, the research revealed a significant shift among students from perceiving leadership as a positional role to understanding it as a lifelong personal journey of growth and societal responsibility. The findings suggest that, in addition to developing leadership competencies, the course facilitated personal transformations by exploring the alignment of personal values, individual leadership styles, and social awareness. A major contribution of this paper is a model that maps a path for students’ leadership growth, beginning with self-awareness, moving to the development of personal philosophy on leadership, and, finally, building practical skills.The findings of this study have broad interdisciplinary applications, highlighting the importance of fostering self-awareness and developing leadership philosophies to prepare students for navigating complex challenges and leading effectively in diverse fields. Universities and educators may consider integrating reflective teaching methods that encourage transformative learning. Such pedagogical approaches can support students in leading authentically, adapting their leadership to various contexts, and maintaining a strong commitment to ethical practices and positive societal impact.